1986
DOI: 10.1021/jm00153a006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amino acids and related compounds. 29. Synthesis and hypolipidemic activities of 5-thienyl-4-oxazoleacetic acid derivatives

Abstract: A series of 2,5-disubstituted 4-oxazoleacetic acid derivatives was synthesized and evaluated for hypolipidemic activity. Among them, those with a thienyl group at C-5 of the oxazole ring exerted highly potent hypolipidemic effects in rats. 2-(4-Fluorophenyl)-5-(3-thienyl)-4-oxazoleacetic acid (88) was the most potent derivative: it was about 2 times as active in normal SD male rats and about 4 times as active in hereditary hyperlipidemic rats (THLR/1) as clofibrate with an improved antiarteriosclerosis index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Eluent: petroleum ether/ethyl acetate (5:1). 12 White solid (54.5 mg, 76%), mp: 123− 124 °C (lit. 12 124−125 °C).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Eluent: petroleum ether/ethyl acetate (5:1). 12 White solid (54.5 mg, 76%), mp: 123− 124 °C (lit. 12 124−125 °C).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…12 White solid (54.5 mg, 76%), mp: 123− 124 °C (lit. 12 124−125 °C). 1 H NMR (400 MHz, CDCl 3 ) δ 7.98 (d, J = 7.6 Hz, 2H), 7.88 (d, J = 7.2 Hz, 2H), 7.60 (t, J = 7.2 Hz, 1H), 6H),4.92 (d,J = 4.4 Hz,2H).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that phenoxy acetic acid pharmacophore has been frequently used in the synthesis of hypolipidemic agent (4–6). Phenoxy acetic acid moiety was frequently coupled with heterocyclic nucleus such as pyrimidine (7), piperidine (8), pyridine (9), oxazole (10), indole (11), benzothiophene (12), benzisoxazole (13), and oxadiazole (14), which exhibited potent antihyperlipidemic activity.…”
mentioning
confidence: 99%